Supply chain process in Meena Bazar: a focus on demand forecasting, inventory management, and reverse and return logistics - Alam, Mohammad Saquib Shahmat (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2023.